i really do not understand this please help me.

## (6x2 - 4x + 11)(5x - 8) please simplify this

# 3 Answers

First multiply each term in the first parenthesis by only the first term in the second parenthesis.

6x^{2} * 5x = 30x^{3}

-4x * 5x = -20x^{2}

11 * 5x = 55x

Next multiply each term in the first parenthesis by only the second term in the second parenthesis.

6x^{2} * -8 = -48x^{2}

-4x * -8 = 32x

11 * -8 = -88

Now add all of your like terms or the terms that have the same degrees.

x^{3}s x^{2}s xs coefficients (or no x just a number)

30x^{3} -20x^{2} 55x

+ -48x^{2} + 32x -88

30x^{3 } -68x^{2} 87x -88

So, your answer is:

30x^{3} - 68x^{2} + 87x - 88

Multiply out all the terms as such:

5x(6x2 - 4x +11) - 8(6x2 - 4x + 11)

30x3 - 20x2 + 55x - 48x2 + 32x - 88

Collect similar terms:

30x3 - 68x2 + 87x + 88 ยป Answer

What you have to do in such a case, is to muliply each term of each factor by each term of other factors. As ax+bx = (a+b)x, (a+b)(x+y) = (a+b)x+(a+b)y = ax+bx+ay+by, so (a+b)(x+y) = ax+ay+bx+by.

Here, one way is to first distribute 5x and -8, which means that

(6x^{2}-4x+11)(5x-8) = 5x(6x^{2}-4x+11)-8(6x^{2}-4x+11), then multiply 5x by 6x^{2}, by -4x and by 11, and multiply -8 by each term too. You'll have 5x(6x^{2}-4x+11)-8(6x^{2}-4x+11) = 30x^{3}-20x^{2}+55x-48x^{2}+32x-88.

Finally, add the coefficients of each degree of x to have 30x^{3}-68x^{2}+87x-88

(6x^{2}-4x+11)(5x-8) = 30x^{3}-68x^{2}+87x-88